(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Legal aid refers to assistance given to low-income and otherwise disadvantaged individualsso that they may use the legal system to uphold their rights. If we are serious about helping theeconomically disadvantaged, we must provide them with access to legal counsel both within and outsideof the judicial system. The Preamble to India’s constitution lays forth the document’s overarching goalto protect the social, economic, and political rights of Indian citizens. Free or low-cost legalrepresentation is provided to those who cannot otherwise afford it as part of legal assistance. Thepreamble of India’s constitution declares that its overarching goal is to ensure the social, economic, andpolitical fairness of the Indian people. The main concept of providing free legal service is to help theneedy people those who are not able to afford an advocate for the justice. As in India, there is a lot ofpoverty and people are so poor that they are no able to afford an advocate so free legal aid is necessaryto those.